Research Development Process in Yangsisurach Health Network, Yangsisurach District, Mahasarakham Province - Chanthanui, Kanjana; Pinatha, Chayanisa; Inmong, Pakpoom; Dana, Kamthorn; Chumnanborirak, Phadoongsit (Journal of Health Science of Thailand, 2019)
This action research aimed to find the process for research development and to evaluate its results in Yangsisurach Health Network, Yangsisurach district, Mahasarakham province. It was conducted from 2014 to 2017. Research participants were purposively selected to include administrators, researchers, supervisors, sub-distric health promoting hospital directors, and co-researchers, altogether 85 persons. The research tools included in-depth interviews, questionnaire survey, after action review, field notes, as well as satisfaction and attitude assessment form. Quantitative data were analyzed by descriptive statistics such as mean, standard deviation, paired t-test; and qualitative data were analyzed through data triangulation and content analysis. It was found that the research development process in the context of the area was the knowledge management (KM) and appreciative inquiry (AI) wih the involvement of facilitators (FA). It began by identifying good things in the workplace through narrative, writing, story telling for inspirational experiences, buddy teaching and support academic resources, Line group for creative learning. Training for presentation was arranged through formal and informal learning forum for researchers to share their feelings and experiences. In the first presentation stage, facilitator and researcher teams suport each other in the whole process. After the first stage, researchers expressed their feeling after the presentation, and reflection on what needs to be done to improve their performance; KM forums were organized for continued improvement of the researchers. It was found that (1) the researchers were highly satisfied with the process. Their attitude toward the research was significantly higher than before the participation. As for the outcomes, there were 35 new researchers, 77 research studies, and 12 research products were published, (2) There was expansion of research ability in all sections and a strong research team, and (3) The outcomes showed that good quality of life in the patients, and reduce exacerbation of illness.In conclusion, the research development process with KM and AI was contectually suitable for the area resulting in the improvement of patient care and the provision of appropriate services widely acknowledged by the public.